Hypoglycemia in diabetic type 2 practitioners physical exercise - Ferreira Neta, Jacy Souto Maior (2017)
Introduction: Hypoglycaemia is, in fact, the most frequent side effect of diabetes treatment, and the main obstacle to optimizing glycemic control. Objective: The objective of this study was to identify episodes of hypoglycemia in type 2 diabetics practicing physical exercise. Methods: Descriptive, quasi-experimental research. Sample was composed of 18 women with type 2 diabetes, participants of the Sweet Life Project - Supervised Exercise Exercise for Diabetics of the ESEF / UPE. The combined aerobic training program lasted 38 weeks. Blood glucose monitoring was performed before and immediately after the training sessions. Statistical analysis was descriptive, with absolute frequency evaluation. Results: After analyzing all the training, 233 hypoglycemia was identified, 19 moderate hypoglycemia, 214 mild hypoglycaemia. There were no cases of severe hypoglycemia. Conclusion: Finally, aerobic, resisted and combined physical training may cause mild to moderate hypoglycemia in type 2 diabetics of this sample, mainly aerobic physical training, which obtained a greater number of hypoglycemias.